Brief historical notes - Andrade, Carmen (Revista ALCONPAT, 2018)
Anniversaries are a good excuse to make some summaries of historical events. Very briefly, some advances made from the initial research in the speciality of reinforcement corrosion which started in the 60’s are summarized. The use of electrochemical techniques was a milestone which enabled, from the decade of the 1970, to study the effect of each variable with much more rigour. The studies on service life started in the decade of 1980, although they were not of general interest until the next decade. From 1990 RILEM Committees and the Iberoamerican Program on Corrosion of CYTED extended the knowledge so widely that in the XXI century the subject attracts much research interest.